2022
DOI: 10.1111/ijfs.15757
|View full text |Cite
|
Sign up to set email alerts
|

Non‐conventional fermentation at laboratory scale of cocoa beans: Using probiotic microorganisms and substitution of mucilage by fruit pulps

Abstract: In a non-conventional lab-scale fermentation of cocoa beans using probiotic microorganisms and substituting the cocoa pulp for fruit pulp, physicochemical, microbiological and quality parameters were investigated. Two hundred grams of beans were fermented in a controlled environmental chamber (temperature ramp rate of 25°C for 48 h; 35°C for 48 h and 45°C for 48 h; and 65% HR). pH, titratable acid, citric, lactic and acetic acids, as well as sugars and ethanol were measured. A cut test was also performed on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Barbosa Santos et al ( 2021) reported that glucose and fructose are the main sugars present in passion fruit and banana, which explains their high levels in this modified fermentation. Other authors observed a different behavior, where the main sugar was sucrose, while glucose and fructose were at low concentrations (Ho et al, 2015;Vizcaino-Almeida et al, 2022). These values may vary depending on the origin of the cocoa, method of determination, degree of maturity of the pulps, sample preparation, type and time of fermentation, and microbial activity (Verce et al, 2021).…”
Section: Dynamic Of Organic Acids and Sugars During Controlled Labora...mentioning
confidence: 99%
See 2 more Smart Citations
“…Barbosa Santos et al ( 2021) reported that glucose and fructose are the main sugars present in passion fruit and banana, which explains their high levels in this modified fermentation. Other authors observed a different behavior, where the main sugar was sucrose, while glucose and fructose were at low concentrations (Ho et al, 2015;Vizcaino-Almeida et al, 2022). These values may vary depending on the origin of the cocoa, method of determination, degree of maturity of the pulps, sample preparation, type and time of fermentation, and microbial activity (Verce et al, 2021).…”
Section: Dynamic Of Organic Acids and Sugars During Controlled Labora...mentioning
confidence: 99%
“…The mixture was thoroughly homogenized and incubated for one hour at ambient temperature (30 °C). Once the mucilage was removed, the cocoa beans were mixed with passion fruit and banana pulps, according to the protocol described by Vizcaino-Almeida et al (2022). The cocoa beans fruit pulps mixture was placed in plastic containers and left for four hours (mixing every 30 minutes) outdoors, allowing the inoculation with the native microorganisms present in the environment.…”
Section: Controlled Laboratory Fermentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ahrert Eskes is the main applicant in patent document WO2009103137A2 [31], which proposes a process to obtain fermented cocoa beans with modified flavors through the addition of aromatic substances such as fruits and pulps during the cocoa bean fermentation process. Positive changes in acidity, sugars, and acids were observed in cocoa beans of the CCN-51 variety, traditionally known as bulk cocoa, fermented with probiotic microorganisms, passion fruit (Passiflora edulis), and banana (Musa paradisiaca) at a laboratory scale for six days [32]. The substitution of cocoa pulp with an artificial cocoa pulp medium during cocoa bean fermentation has also been used to study various fermentation conditions that may improve the quality of cocoa beans [33].…”
Section: Food Sciencementioning
confidence: 99%
“…The top 10 authors presented in Figure 6 are responsible for 30.3% of the publications and are from Belgium (49), Germany (39), Brazil (32), Ghana (14), and France (13). Luc De Vuyst (33) from Belgium and Rosane Schawn (22) from Brazil lead in journal publications on cocoa fermentation.…”
Section: Authors and Universitiesmentioning
confidence: 99%